A subset of clones in the chick telencephalon arranged in rostrocaudal arrays. - Szele, F; Cepko, C (1996)
BACKGROUND: Different areas of the vertebrate central nervous system appear to follow different rules during development for determining the position of sibling cells. For example, in the chick hindbrain, clones are frequently confined to a single functional unit that derives from a single rhombomere. In contrast, clones in the mammalian cerebral cortex often cross functional boundaries because of the extensive migration of sibling cells in orthogonal directions. We have investigated whether the pattern of clonal distribution in the chick telencephalon is similar to that of the hindbrain or to the more functionally analogous mammalian cerebral cortex. Progenitor cells in the chick telencephalon were marked using a retroviral library encoding alkaline phosphatase and over 10(5) distinct molecular tags. Patterns of dispersion were detected using alkaline phosphatase histochemistry, followed by the recovery and sequencing of the molecular tag. We also analyzed the phenotypes of cells that occurred within the clones. RESULTS: A subset of progenitors gave rise to clones that were found in rostrocaudal arrays resembling tubes. Arrays were restricted in the mediolateral and dorsoventral planes but could span up to 4 mm in the rostrocaudal direction. They were found throughout the telencephalon and a single clone often spanned more than one telencephalic nucleus. Rostrocaudal clones comprised 60% of clones containing five or more cells and contained many different types of neurons, astrocytes, oligodendrocytes, or various combinations of these cell types. CONCLUSIONS: Telencephalic progenitors are multipotent, producing progeny that become distinct cell types. Clonally related cells can migrate rostrocaudally within domains that are restrained in the mediolateral and dorsoventral directions. A subset of rostrocaudal clones resemble those seen in the mammalian cerebral cortex, with respect to the crossing of functional boundaries, but all rostrocaudal clones differ from the cerebral cortical clones in the pattern of spread of sibling cells, with the rostrocaudal clones being more constrained in the mediolateral and dorsoventral directions. A role for lineage in the patterning of the chick forebrain is supported by these observations. In addition, these data suggest a role for cues within the telencephalic marginal zone that serve to guide clones in their rostrocaudal migration.